ANALISIS SEKTOR EKONOMI UNGGULAN DI PROVINSI SUMATERA UTARA - Monika Karolina Sianturi; Fitri Annisa Harahap (Jurnal Ilmu Ekonomi, 2021)
The economic sector plays an important role in national development. In order to experience a paradigm shift in more advanced national development, a plan or strategy is needed to encourage economic growth. It is important to explore and identify the potential development of the regional economic sector which is used as a superiority to provide direction and decision-making materials for the parties in creating added value and competitiveness of the leading sector. Therefore, this study aims to analyze what economic sectors are based on superior sectors or sectors that play a greater role as a trigger for regional economic development in North Sumatra Province from 2015 to 2019. The type of data used in this study is secondary data in the form of data. GRDP of the economic sector of North Sumatra Province which is contained in the Central Statistics Agency (BPS) of North Sumatra Province. The analysis method used is Location Quetiont (LQ) and Shift Share. The results of this study indicate that North Sumatra Province has five leading sectors, namely agriculture, forestry and fisheries; water supply, waste management, waste and recycling sectors; construction sector; wholesale and retail trade, car and motorcycle repair; and the real estate sector. The agriculture, forestry and fisheries sectors are the largest contributions in North Sumatra Province from the overall analysis carried out.